2023
DOI: 10.1017/s0960258523000144
|View full text |Cite
|
Sign up to set email alerts
|

Seed anatomy and dormancy class of 14 species from the Andean montane forests of Colombia

Abstract: Seed dormancy is a key trait used around the world to help understand the ecological dynamics of plant species, however, in some ecosystems such as the Andean forests of Colombia, the identification of dormancy class remains poorly known. To address this, we described the morphology, anatomy and dormancy class of the seeds and fruits of 14 species using microtome sections, light microscopy and scanning electron microscopy. Five native pioneer species showed Morphophysiological Dormancy, three Physical Dormancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The authors found dormancy in 85% of their study species, three of which are in the genera Cecropia and were classified as having both physiological and physical dormancy (referred to as physiophysical dormancy). Seeds with physiophysical dormancy have impermeable coats, a fully developed embryo, and a mean germination time (MGT) of over 30 days (Rojas-Villa and Quijano-Abril, 2023). Here, we present seed permeability data measured by fluorescent dye uptake into the seed endosperm and germination trails from a Panamanian lowland population of Cecropia peltata (one of the species studied by Rojas-Villa & Quijano-Abril, 2023), as well as Ochroma pyramidale, Cecropia longipes, and Cecropia insignis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found dormancy in 85% of their study species, three of which are in the genera Cecropia and were classified as having both physiological and physical dormancy (referred to as physiophysical dormancy). Seeds with physiophysical dormancy have impermeable coats, a fully developed embryo, and a mean germination time (MGT) of over 30 days (Rojas-Villa and Quijano-Abril, 2023). Here, we present seed permeability data measured by fluorescent dye uptake into the seed endosperm and germination trails from a Panamanian lowland population of Cecropia peltata (one of the species studied by Rojas-Villa & Quijano-Abril, 2023), as well as Ochroma pyramidale, Cecropia longipes, and Cecropia insignis.…”
mentioning
confidence: 99%
“…Seeds with physiophysical dormancy have impermeable coats, a fully developed embryo, and a mean germination time (MGT) of over 30 days (Rojas-Villa and Quijano-Abril, 2023). Here, we present seed permeability data measured by fluorescent dye uptake into the seed endosperm and germination trails from a Panamanian lowland population of Cecropia peltata (one of the species studied by Rojas-Villa & Quijano-Abril, 2023), as well as Ochroma pyramidale, Cecropia longipes, and Cecropia insignis. Our data do not support the presence of physical dormancy in seeds of Cecropia, while O. pyramidale does exhibit physical dormancy.…”
mentioning
confidence: 99%